College Students' Reasons for Depression Nondisclosure in Primary Care. Issue 3 (2nd July 2016) - Meyer, William J.; Morrison, Patrick; Lombardero, Anayansi; Swingle, Kelsey; Campbell, Duncan G.
ABSTRACT: Unwillingness to share depression experiences with primary care physicians contributes to the undertreatment of depression. This project examined college students' reasons for depression nondisclosure to primary care providers (PCPs). Undergraduate participants read a vignette describing someone with depression and completed measures of disclosure barriers. Analyses indicated 26% of respondents would NOT disclose depression symptoms to PCPs. Reasons for nondisclosure included difficulty initiating the depression conversation, medication aversion, and fear of referral to a psychologist. Also, anger toward the vignette character varied with disclosure willingness, suggesting that nondisclosers feel more stigma than disclosers and are less likely to engage in psychotherapy. Because engagement in pharmacological and/or psychotherapeutic treatment requires identification of depression in healthcare settings, increased understanding of disclosure barriers could increase students' access to depression treatment.